Nic 8 políticas contables, cambios en las estimaciones contables y errores y su correcta aplicación en el ámbito empresarial. - Barba Mendoza, Valeria Valentina (Machala : Universidad Técnica de Machala, 2022)
The International Financial Reporting Standards (IFRS) as well as the International Accounting Standards (IAS) were implemented in the world of commerce in order to obtain financial reports that faithfully represent financial performance, cash flow and equivalents; and the current financial situation in which a company finds itself, since from the information obtained an exhaustive analysis and decision-making by the administration is carried out. The application of the International Accounting Standard (IAS) 8 Accounting policies, changes in accounting estimates and errors allows establishing the judgments for the implementation or change of an accounting policy in an entity, as well as its accounting treatment. In addition, it contributes to obtaining relevant information about changes in accounting policies, estimates and the correction of errors for its correct adjustment or explanatory note, depending on the prospective or retroactive nature according to the standard, at the end of an accounting period. The purpose of this investigation is to analyze the changes due to accounting policies, estimates and accounting errors", based on what is established in IAS 8 "Accounting policies, changes in accounting estimates and errors", in order to give a correct application in the professional field; and in turn, serve as a support guide for the university community for future inquiries, since it starts from theoretical bases of bibliographic sources to the application of the practical case that will allow a better understanding regarding the adaptation of the regulations.
Las Normas Internacionales de Información Financiera (NIIF) al igual que las Normas Internacionales de Contabilidad (NIC) se implementaron en el mundo del comercio con el fin de obtener informes financieros que representen fielmente el rendimiento financiero, el flujo de efectivo y equivalentes; y la situación financiera actual en la que se encuentra una compañía, puesto que a partir de la información obtenida se procede al análisis exhaustivo y toma de decisiones por parte de la administración. La aplicación de la Norma Internacional de Contabilidad (NIC) 8 Políticas contables, cambios en las estimaciones contables y errores permite establecer los juicios para la implementación o cambio de una política contable en una entidad, así como también su tratamiento contable. Además, contribuye a la obtención de información relevante acerca de modificaciones en políticas contables, estimaciones y la corrección de errores para su correcto ajuste o nota aclaratoria, dependiendo el carácter prospectivo o retroactivo según la norma, al finalizar un periodo contable. El fin de esta investigación es analizar los cambios por políticas contables, estimaciones y errores contables”, con base en lo que establece la NIC 8 “Políticas contables, cambios en estimaciones contables y errores”, con el fin de dar una correcta aplicación en el campo profesional; y a su vez, sirva de guía de apoyo a la comunidad universitaria para futuras indagaciones puesto que, que parte de bases teóricas de fuentes bibliográficas hasta la aplicación del caso práctico que permitirá un mejor entendimiento en cuanto a la adaptación de la normativa.
Keywords: CONTABILIDAD; NIC 8; ESTIMACIONES CONTABLES